Pengembangan Rencana Pelaksanaan Pembelajaran Matematika Kurikulum 2013 Berbasis Lesson Study Di SMP - Sutama Sutama (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2016)
The purpose of research, describe and test the development of lesson plan Junior High School math curriculum-based lesson study in 2013. This type of research, namely research and development. The subject of research, math teachers, principals, and students from Junior High School 26 Salatiga, as well as education experts and policy makers. Methods of data collection, observation, interviews, documentation, testing, and questionnaires. Data were analyzed using qualitative analysis flow models, comparison, and t test. Result: the planning of the implementation of learning methods section, learning activities, and part of the cover varies greatly from one teacher to another. In the method of a teacher who wrote approach, learning strategies, and learning methods; but there is also a write down approach, a model of learning and teaching methods. The learning activities are structured in a math teacher lesson plan through three stages: preliminary activities, core activities, and closing activity. At each step of the variation of teacher is very diverse, but not pay attention to individual differences of students. At the closing, the teacher with students either individually or in groups do not reflect to evaluate the entire range of activities hereinafter find direct benefit aupun indirectly from the learning outcomes, provide feedback on the learning process and results, conduct follow-up activity in the form of duties , either individually or in groups, and inform future learning plans.